Generation mean analysis for seed yield and its component traits in five crosses of castor (Ricinus communis L.): GENERATION MEAN ANALYSIS FOR SEED YIELD AND ITS COMPONENTS IN FIVE CROSSES OF CASTOR - J R PATEL; DIXITA K PATEL; D A PATEL; K V PATEL (Journal of Oilseeds Research, 2021)
The present study was carried out to estimate gene effect, heterosis, inbreeding depression, heritability and expected genetic advance for seed yield and its component characters in five crosses of castor (Ricinus communis L.). The analysis of variance revealed significant differences among different crosses and among different generations within cross for all the characters studied. In the present study, both additive and non-additive gene actions were found to be important for the expression of seed yield and most of its component traits indicating that intermating among the selected segregants to break the undesirable linkage followed by one or two generations of selfing could facilitate the accumulation of favorable alleles for the improvement of these traits. However, some of the characters in various crosses were governed by fixable (additive and additive x additive) gene effects and hence, these characters could be improved through pedigree method of selection. Significant heterosis and heterobeltiosis in desired direction observed for seed yield and its majority of the components viz., number of total and effective branches/plant, number of capsules on primary raceme, shelling out turn and 100-seed weight suggested the possibility of utilizing hybrid vigour on commercial scale. High estimates of broad as well as narrow sense heritability along with high genetic advance observed for seed yield/plant in cross I (SKI 324 x PCS 124), cross II (ANDCI 10-7 x JH 109) and cross V (ANDCI 10-7 x SKI 324) suggested the preponderance of additive/fixable gene effect and hence this character could be further improved by adopting selections in succeeding segregating generations. The combination of low narrow sense heritability along with low genetic advance detected for few characters indicated the major role of non-additive gene action and therefore, heterosis breeding or population improvement approach would be more effective for the improvement of these traits. It is being suggested that the parental genotypes SKI 324, ANDCI 10-7 and ANDCI 8 due to their presence in high heterotic combinations viz., ANDCI 10-7 x JH 109 and ANDCI 8 x SKI 324 need to be further exploited in future castor breeding programme.